The dynamics of Africa’s fruit and vegetable processing sectors - Schreinemachers, Pepijn; Ambali, Mwasilwa; Mwambi, Mercy; Olanipekun, Caleb Ibukun; Yegbemey, Rosaine Nerice; Wopereis, Marco C.S. (AKADEMIYA2063, 2022)
The production of fruits and vegetables (F&V) in Africa has increased 3.3 percent annually during the last 20 years, but only 0.7 percent in per capita terms (FAOSTAT 2022; Figure 3.1). Africa has the lowest per capita production and consumption of F&V in the world, although South Africa, Morocco, and Egypt are large producers and exporters.